Business Plan of Cafe de Laundry / Taariq Murad … [et al.] - Murad, Taariq; Abdul Hanif, Hairul Nabeel Iskandar; Muhamed, Ahmad Junaidi; Shamsudin, Ahmad Zaki (2000)
The term coin laundry is defined as a "commercial grade self-service laundry". The equipment is placed into service retail space. Coin operated laundries are a unique and small business in that they have no inventory of receivables, and no traditional employees. A minority of coin laundry busineses employs attendants. Laundry service is a must exist type of business in other words it is a necessity of life. The factors that has forced our "eye-sight" towards this business is because of the position of the business that complies with the demand and the nature of the business that act as a necessity in life. Besides all that it also provides a basic health service for the public.